TINGKAT PENGETAHUAN KEPALA KELUARGA MEMILIKI HUBUNGAN DENGAN STATUS KONDISI RUMAH - Warseno, Agus (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
The percentage of qualified house health in Indonesia in 2014 only reached 61.81% Home health conditions are determined by one of the family members' knowledge and understanding of a healthy home itself. The The objection of this study is to find out the relation of knowledge of family head about healthy house with the house condition in Kersan, Triwidadi Village, and District of Pajangan Bantul. The research design was observational with cross sectional. Sample taken by total sampling technique as many 72 family head in Kresan, Bantul. Research instrument was questioner and observation sheet. Research result analyzed by chi square test. The results of this study note the level of knowledge of the head of the family about healthy homes, most of the categories are as low as 29 people (40.3%). Most of the housing conditions are unhealthy houses as many as 50 houses (69.4%). Result of chi square test between knowledge and the house condition obtained ρ as much 0,002. In conclusion, the level of knowledge of the head of the family about a healthy home is related to the condition of the house.